THE ROLE OF PARONYMS IN INDEPENDENT LEXEMES - Yusupova Soxiba Islombek qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article studies the use of paronyms in independent word classes in the Uzbek language and their lexical and semantic properties. The formal similarities and differences in meaning of paronyms, as well as their correct and incorrect use in the speech process are analyzed. During the study, paronyms found in independent word classes such as nouns, adjectives, verbs and adverbs are considered on the basis of examples, and their role in the formation of speech culture is highlighted. The results of the article are of theoretical and practical importance for linguistics, in particular, lexicology and applied linguistics.